O resultado da análise da densidade básica da madeira é influenciado pelo método de determinação e tipo de amostra? - Arantes, Bruno Sangali (2024)
Wood basic density is a crucial parameter for the viability of industries in the forestry sector, particularly in pulp production. However, the time required to saturate wood samples before analysis remains a significant challenge. Existing technical standards have gaps that lead to the adoption of different samples, saturation methods, and methodologies for determining basic density, resulting in variations in the outcomes. This study aimed to analyze the effect of different methods, sample types, and saturation parameters on the determination of the basic density of eucalyptus wood and how they interfere with the prediction of parameters in the pulp industry. The study involved the analysis of five eucalyptus clones (E. grandis, E. urophylla, and their hybrids) aged 6.8 years, originating from an experimental plot in São Miguel Arcanjo, São Paulo. Five trees per clone were collected, sampled at different positions along the commercial stem, generating discs and chips. The basic density of the discs was determined by the hydrostatic balance method, while the chips were analyzed using both the hydrostatic balance method and the maximum moisture content method, with saturation checked every three days, except for tests 2 and 3, which began on the fourth day, using constant mass and submersion methodologies. The results showed that the saturation method significantly influences the basic density values obtained by the maximum moisture content method, with differences of up to 28.27 kg/m³. Although the saturation tests did not significantly impact the final basic density values, tests 2 and 3 reduced the saturation time to six days, while the others varied between 9 and 15 days. The difference in basic density between wedges and chips was significant only for clone C2, with an average difference of up to 10.78 kg/m³ across all clones. Test 3, using vacuum, pressure, and a temperature of 100°C, produced the best results. The sample type, saturation criterion, and determination method proved to be factors of variability in wood basic density, and this variability led to consequences in the prediction of specific consumption